Galactose uncovers face recognition and mental images in congenital prosopagnosia: The first case report. (September 2014) - Esins, Janina; Schultz, Johannes; Bülthoff, Isabelle; Kennerknecht, Ingo
<x content-type="archive" xml:space="preserve">Abstract</x> A woman in her early 40s with congenital prosopagnosia and attention deficit hyperactivity disorder observed for the first time sudden and extensive improvement of her face recognition abilities, mental imagery, and sense of navigation after galactose intake. This effect of galactose on prosopagnosia has never been reported before. Even if this effect is restricted to a subform of congenital prosopagnosia, galactose might improve the condition of other prosopagnosics. Congenital prosopagnosia, the inability to recognize other people by their face, has extensive negative impact on everyday life. It has a high prevalence of about 2.5%. Monosaccharides are known to have a positive impact on cognitive performance. Here, we report the case of a prosopagnosic woman for whom the daily intake of 5 g of galactose resulted in a remarkable improvement of her lifelong face blindness, along with improved sense of orientation and more vivid mental imagery. All these improvements vanished after discontinuing galactose intake. The self-reported effects of galactose were wide-ranging and remarkably strong but could not be reproduced for 16 other prosopagnosics tested. Indications about heterogeneity within prosopagnosia have been reported; this could explain the difficulty to find similar effects in other prosopagnosics. Detailed analyses of the effects of galactose in prosopagnosia might give more insight into the effects of galactose on human cognition in general. Galactose is cheap and easy to obtain, therefore, a systematic test of its positive effects on other cases of congenital prosopagnosia may be warranted.